2017
DOI: 10.1111/bph.13888
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in the heart: insights into mechanisms and drug targets

Abstract: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
94
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 120 publications
(141 reference statements)
1
94
0
2
Order By: Relevance
“…It is well-established that the ischemia/reperfusion-induced injury in organs such as heart and brain is closely related to activation of neutrophils/macrophages and extensive releases of pro-inflammatory cytokines and inflammasome [27][28][29]. During this procedure, oxidative stress and endoplasmic reticulum stress also contribute to the cardiac injury [30,31]. The relationship between inflammation and cardiac arrest has been investigated extensively [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that the ischemia/reperfusion-induced injury in organs such as heart and brain is closely related to activation of neutrophils/macrophages and extensive releases of pro-inflammatory cytokines and inflammasome [27][28][29]. During this procedure, oxidative stress and endoplasmic reticulum stress also contribute to the cardiac injury [30,31]. The relationship between inflammation and cardiac arrest has been investigated extensively [32].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Among these, excessive accumulation of ROS could cause severe oxidative stress injury directly leading to cell death. 13,14 Hence, inhibiting ER stress-induced apoptosis maybe an effective way to alleviate myocardial injury. 11 A series of studies have shown that apoptosis in myocardial injury is also associated with endoplasmic reticulum (ER) stress injury.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are a large number of calcium channels on cardiomyocytes. During excitation under physiological conditions, calcium influx through L-type calcium channels is important and responsible for further calcium influx from internal stores (43)(44)(45). However in the presence of ischemia and hypoxia, calcium influx through L-type calcium channels increases and leads to further calcium overload from internal stores during reperfusion, leading to irreversible pathological changes, including cell necrosis and apoptosis (46,47).…”
Section: Discussionmentioning
confidence: 99%